Degradable automobile recycled plastic product and preparation method thereof
By using composite reinforcement agents in polylactic acid plastics, combined with allylamine, 4-chlorobenzene boric acid and thiolated carbon nitride @MXene QDs and other materials, the problem of insufficient flame retardant performance and degradation rate of polylactic acid plastics is solved, and the problem of insufficient flame retardant performance and degradation rate of polylactic acid plastics is achieved. Efficient flame retardant and rapid degradation effects reduce production costs.
Patent Information
- Application Number
- CN202411651223.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-14
AI Technical Summary
Polylactic acid plastics have shortcomings in flame retardant performance and degradation rate, and it is difficult to meet the needs of high flame retardant performance requirements and rapid degradation.
Using composite enhancers, the synergistic effect of allylamine, 4-chlorobenzene boric acid, dimethyl phosphate and thiolated carbon nitride @MXene QDs and other materials can be synthesized to improve the resistance of plastics. The flame retardant and degradation rate are enhanced through the layered structure and photocatalytic action of the nanosheets.
It significantly improves the flame retardant performance and degradation rate of plastic products, achieves excellent flame retardant performance and degradability performance, and reduces production costs.
Smart Images

Figure BDA0005140981120000101 
Figure BDA0005140981120000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic products, and in particular to a degradable automobile recycled plastic product and a preparation method thereof. Background Art
[0002] Plastic products are an indispensable part of people's daily lives, but the use of a large number of plastic products will cause plastic pollution. In the automotive manufacturing industry, plastics are widely used in interior and exterior trims, electronic equipment housings, etc., which not only increases the consumption of plastics, but also increases the difficulty of handling plastic waste. Degradable plastics are a new type of environmentally friendly material that can be decomposed by microorganisms under certain conditions to reduce pollution to the environment. Therefore, recycling and reusing automotive plastics and introducing degradable plastics into the synthesis process can not only reduce environmental pollution, but also save resources and reduce production costs.
[0003] As one of the most studied biodegradable plastics, polylactic acid plastic has excellent biodegradability, environmental protection, safety, good processing performance, a wide range of applications and unique physical properties. However, polylactic acid plastic still has some disadvantages, such as: 1) limited flame retardancy, which is not conducive to its application in fields with high flame retardancy requirements; 2) low degradation rate, which is because polylactic acid is degraded by hydrolysis of the main chain ester group, and the degradation rate is affected by the molecular weight, molecular weight distribution, crystallinity, morphology, diffusion rate of water into the polymer, and stereoisomer content of polylactic acid. Therefore, it is necessary to deal with its shortcomings and develop a plastic product with excellent flame retardancy, high degradation rate and other advantages. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a degradable automobile recycled plastic product and a preparation method thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A degradable automobile recycled plastic product, comprising the following raw materials in parts by weight: 50-60 parts of polylactic acid, 10-15 parts of automobile recycled plastic particles, 5-10 parts of a composite reinforcing agent, 1-2 parts of a silane coupling agent, 0.8-1 parts of an antioxidant, 1-2 parts of a lubricant, and 1-3 parts of a toughening agent;
[0007] The composite reinforcing agent is prepared by the following steps:
[0008] Step A1, adding allylamine, triethylamine and dichloromethane into a reactor and stirring to disperse, then slowly adding 4-chlorophenylboric acid and stirring for 30-50 minutes, and reflux reaction at 40-45°C for 6 hours and continue at room temperature, and continue the reaction at room temperature for 10-14 hours. After the reaction is completed, centrifuge, wash and dry to obtain intermediate 1;
[0009] Step A2, disperse the intermediate 1, dimethyl phosphate and N,N-dimethylformamide evenly in a reactor, raise the system temperature to 110-120°C, continue stirring and react for 5-7h, and after the reaction is completed, rotary evaporate and dry to obtain a terminal olefin flame retardant;
[0010] Step A3, adding thiolated carbon nitride @MXene QDs and terminal olefin flame retardant into deionized water and dispersing them evenly, recorded as solution 1; dispersing nonylphenol polyoxyethylene ether and ethoxylated alkylphenol ammonium sulfate in deionized water, stirring for 30 minutes, slowly adding solution 1 under nitrogen conditions, and at the same time dropping 0.001-0.005 mol / L triethylamine aqueous solution, and adjusting the pH to 9.5-10, raising the system temperature to 75-85°C, reacting for 8-9 hours, and after the reaction is completed, filtering, washing, and drying to obtain a composite reinforcing agent;
[0011] Further, in step A1, the usage ratio of allylamine, triethylamine, dichloromethane and 4-chlorophenylboric acid is 0.12-0.32 mol: 0.15-0.4 mol: 100 mL: 0.1-0.3 mol;
[0012] Further, in step A2, the usage ratio of intermediate 1, dimethyl phosphate and N,N-dimethylformamide is 0.1-0.2 mol: 0.2-0.4 mol: 200 mL;
[0013] Furthermore, in step A3, the mass ratio of nonylphenol polyoxyethylene ether, ethoxylated alkylphenol ammonium sulfate, deionized water, solution 1 and triethylamine aqueous solution is 1-2:1:100:100:10; the amount ratio of thiolated carbon nitride @MXene QDs, terminal olefin flame retardant and deionized water in solution 1 is 1g:2.5-3.5g:100g.
[0014] Furthermore, the thiolated carbon nitride@MXene QDs are prepared by the following steps:
[0015] Step B1, placing 6-9 g of urea in an autoclave at 180° C. for 60-90 min. After the reaction is completed, transferring the product to a muffle furnace and heating it to 500° C. at a rate of 2° C. / min. reacting for 3.5-4.5 h. After the reaction is completed, cooling to room temperature, washing to neutrality, and then ultrasonically exfoliating in a mixed solution of ethanol / water with a volume ratio of 1:1 for 6-12 h, and drying to obtain carbon nitride nanosheets;
[0016] Step B2, MXene powder and ethanol were added to a mortar at a mass ratio of 1:0.5 and ground for 20 minutes, then sieved with an 800-mesh sieve, and the sieved MXene material and carbon nitride nanosheets were added to a reactor containing 0.5 mol / L sodium hydroxide ethanol solution, and stirred in a sealed oil bath at 100°C for 3 hours, and then ultrasonically treated for 2-3 hours. After the reaction was completed, centrifuged at a speed of 300-500 rpm for 30 minutes, and the upper layer solution was ultrasonically treated for 2 hours, and then dialyzed for 48 hours, and freeze-dried to obtain carbon nitride @MXene QDs;
[0017] Step B3, dispersing carbon nitride @MXene QDs in deionized water, ultrasonically dispersing, adjusting the pH to 8.5, adding 4-mercaptobenzoic acid, and reacting under nitrogen for 10-12 hours at a reaction temperature of 75-85°C. After the reaction is completed, cooling to room temperature, filtering, washing, and drying to obtain thiolated carbon nitride @MXene QDs;
[0018] Further, the mass ratio of the MXene material, carbon nitride nanosheets and sodium hydroxide ethanol solution after screening in step B2 is 1:0.5-2:30;
[0019] Furthermore, in step B3, the mass ratio of carbon nitride@MXene QDs, 4-mercaptobenzoic acid and deionized water is 1:2-4:50.
[0020] A method for preparing a degradable automobile recycled plastic product comprises the following steps:
[0021] The raw materials are weighed by weight, and recycled plastic particles from automobiles and silane coupling agent are added into a stirrer and stirred evenly. Then polylactic acid, composite reinforcing agent, antioxidant, lubricant and toughening agent are added and mixed evenly. The mixture is then transferred into a twin-screw extruder for melt extrusion, water cooling, pelletizing and drying to obtain plastic particles, which are then subjected to tape casting to obtain plastic products.
[0022] Beneficial effects of the present invention:
[0023] The plastic product of the present invention uses degradable polylactic acid as the main raw material, and adds automobile recycled plastic particles to reduce the use of polylactic acid, reduces the pollution caused by waste plastic particles to the environment through waste utilization, and reduces the production cost; in the composite reinforcing agent, the synergistic effect of the three elements N, P, and B is firstly adopted to improve the flame retardant property of the matrix, and at the same time, the nanosheets with a layered structure are used to synergistically flame retardant, further improving the flame retardant property of the matrix, and the nanosheets introduced in the composite reinforcing agent also have certain photocatalytic properties, which can catalytically degrade macromolecular polymers into small molecular substances, thereby improving the degradation rate of the matrix. Therefore, the plastic product of the present invention not only has excellent flame retardant properties and degradable properties, but also reduces the production cost.
[0024] In the composite reinforcing agent, allylamine and 4-chlorophenylboronic acid are used to react to synthesize intermediate 1; then, an esterification reaction is used to react intermediate 1 with dimethyl phosphate to generate a terminal olefin flame retardant; finally, the thiol group on the surface of thiolated carbon nitride @MXene QDs reacts with the olefin group in intermediate 2 to synthesize the composite reinforcing agent. The addition of the composite reinforcing agent not only increases the degradation rate of plastic products, but also further improves the flame retardant properties of plastic products. The terminal olefin flame retardant is grafted into the thiolated carbon nitride @MXeneQDs, and then the phosphate group, borate group and nitrogen element are introduced into the composite reinforcing agent. The flame retardant properties of the matrix are improved through the synergistic effect of the elements. Among them, the phosphate structure decomposes during combustion and heat to generate polyphosphoric acid and phosphoric acid, thereby promoting the polymer to form a large amount of carbon through cyclization and cross-linking. The dense carbon layer formed can effectively inhibit the generation of salt spray and prevent further combustion of the matrix. The non-combustible gases such as ammonia and nitrogen generated by the nitrogen element during combustion can dilute the combustible gases and oxygen in the air, thereby inhibiting the combustion of the matrix. The borate group forms a glass-like coating on the polymer when heated, thereby achieving flame retardant and smoke suppression effects; carbon nitride @MXene The layered structure of QDs also has a certain flame retardant effect. This is because the layered structure it contains acts as a physical barrier similar to graphene during combustion, effectively extending the diffusion path of the gas, thereby inhibiting the continued combustion of the matrix; in addition, the thiol contained in the composite reinforcing agent can also react with the terminal carboxyl group in the polylactic acid molecular chain to increase the bonding force between the composite reinforcing agent and the polymer, which can effectively avoid the migration and migration of the flame retardant, allowing the flame retardant to continuously and stably exert its flame retardant effect, thereby improving the durability of the flame retardant effect.
[0025] The thiolated carbon nitride @MXene QDs in the composite enhancer also act as a photocatalyst. The photocatalyst breaks the polymer into shorter molecular chains through photocatalytic polymerization, and then degrades the short molecular chains through biodegradation, effectively improving the degradation rate of the matrix. The photocatalyst uses carbon nitride nanosheets as a substrate and utilizes its own good photocatalytic degradation performance of polymers. After loading and modification, the catalyst's utilization rate of visible light is increased, the photocatalyst's ability to generate electron-hole pairs is improved, and the photocatalytic activity is improved. The loading of MXene QDs increases the specific surface area of carbon nitride nanosheets, provides more active sites for photocatalytic reactions, greatly improves the catalytic activity of the photocatalyst, and also reduces the charge transfer resistance of carbon nitride nanosheets, making it easier for the photocatalyst to enter the separation of electron-hole pairs, thereby improving the photocatalytic degradation performance. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] Thiolated carbon nitride@MXene QDs were prepared by the following steps:
[0029] Step B1, placing 6 g of urea in an autoclave at 180° C. for 60 min. After the reaction is completed, the product is transferred to a muffle furnace and heated to 500° C. at 2° C. / min. The reaction is performed for 3.5 h. After the reaction is completed, the product is cooled to room temperature, washed to neutrality, and then ultrasonically peeled in a mixed solution of ethanol / water with a volume ratio of 1:1 for 6 h, and dried to obtain carbon nitride nanosheets;
[0030] Step B2, MXene powder and ethanol were added to a mortar at a mass ratio of 1:0.5 and ground for 20 minutes, then sieved with an 800-mesh sieve, 1 g of the sieved MXene material and 0.5 g of carbon nitride nanosheets were added to a reactor containing 30 g of 0.5 mol / L sodium hydroxide ethanol solution, and stirred in a sealed oil bath at 100 ° C for 3 hours, and then ultrasonically treated for 2 hours. After the reaction was completed, centrifuged at 300 rpm for 30 minutes, the upper layer solution was taken and ultrasonicated for 2 hours, and then dialyzed for 48 hours, and freeze-dried to obtain carbon nitride @MXene QDs;
[0031] Step B3, disperse 1 g of carbon nitride @MXene QDs in 50 g of deionized water, ultrasonically disperse, and adjust the pH to 8.5, then add 2 g of 4-mercaptobenzoic acid, and react under nitrogen for 10 h at a reaction temperature of 75 ° C. After the reaction is completed, cool to room temperature, filter, wash, and dry to obtain thiolated carbon nitride @MXene QDs.
[0032] The composite reinforcing agent is prepared by the following steps:
[0033] Step A1, add 0.12 mol of allylamine, 0.15 mol of triethylamine and 100 mL of dichloromethane into a reactor and stir to disperse, then slowly add 0.1 mol of 4-chlorophenylboric acid and stir for 30 min, and reflux at 40° C. for 6 h and continue to react at room temperature for 10 h. After the reaction is completed, centrifuge, wash and dry to obtain intermediate 1;
[0034] Step A2, 0.1 mol of intermediate 1, 0.2 mol of dimethyl phosphate and 200 mL of N,N-dimethylformamide are evenly dispersed in a reactor, the system temperature is raised to 110° C., and the reaction is continued with stirring for 5 hours. After the reaction is completed, the mixture is rotary evaporated and dried to obtain a terminal olefin flame retardant;
[0035] Step A3, add 1g of thiolated carbon nitride @MXene QDs and 2.5g of terminal olefin flame retardant to 100g of deionized water and disperse them evenly, recorded as solution 1; disperse 1g of nonylphenol polyoxyethylene ether and 1g of ethoxylated alkylphenol ammonium sulfate in 100g of deionized water, stir for 30min, slowly add solution 1 under nitrogen conditions, and at the same time drop 10g of 0.001mol / L triethylamine aqueous solution, and adjust the pH to 9.5, increase the system temperature to 75°C, react for 8h, and after the reaction is completed, filter, wash, and dry to obtain a composite reinforcing agent.
[0036] Example 2
[0037] Thiolated carbon nitride@MXene QDs were prepared by the following steps:
[0038] Step B1, placing 7.5 g of urea in an autoclave at 180° C. for 80 min. After the reaction is completed, transferring the product to a muffle furnace, and heating it to 500° C. at 2° C. / min, reacting for 4 h. After the reaction is completed, cooling it to room temperature, washing it to neutrality, and then ultrasonically peeling it in a mixed solution of ethanol / water with a volume ratio of 1:1 for 10 h, and drying it to obtain carbon nitride nanosheets;
[0039] Step B2, MXene powder and ethanol were added to a mortar at a mass ratio of 1:0.5 and ground for 20 minutes, then sieved with an 800-mesh sieve, 1 g of the sieved MXene material and 1 g of carbon nitride nanosheets were added to a reactor containing 30 g of 0.5 mol / L sodium hydroxide ethanol solution, and stirred in a sealed oil bath at 100 ° C for 3 hours, and then ultrasonically treated for 2.5 hours. After the reaction was completed, centrifuged at 400 rpm for 30 minutes, the upper layer solution was taken and ultrasonicated for 2 hours, and then dialyzed for 48 hours, and freeze-dried to obtain carbon nitride @MXene QDs;
[0040] Step B3, disperse 1g of carbon nitride @MXene QDs in 50g of deionized water, ultrasonically disperse, and adjust the pH to 8.5, then add 3g of 4-mercaptobenzoic acid, and react under nitrogen for 11h at a reaction temperature of 80°C. After the reaction is completed, cool to room temperature, filter, wash, and dry to obtain thiolated carbon nitride @MXene QDs.
[0041] The composite reinforcing agent is prepared by the following steps:
[0042] Step A1, add 0.22 mol of allylamine, 0.25 mol of triethylamine and 100 mL of dichloromethane into a reactor and stir to disperse, then slowly add 0.2 mol of 4-chlorophenylboric acid and stir for 40 min, and reflux at 45 ° C for 8 h, and continue to react at room temperature for 12 h. After the reaction is completed, centrifuge, wash and dry to obtain intermediate 1;
[0043] Step A2, 0.15 mol of intermediate 1, 0.3 mol of dimethyl phosphate and 200 mL of N,N-dimethylformamide are evenly dispersed in a reactor, the system temperature is raised to 115° C., and the reaction is continued with stirring for 6 hours. After the reaction is completed, the reaction is rotary evaporated and dried to obtain a terminal olefin flame retardant;
[0044] Step A3, add 1g of thiolated carbon nitride @MXene QDs and 3g of terminal olefin flame retardant to 100g of deionized water and disperse them evenly, recorded as solution 1; disperse 1.5g of nonylphenol polyoxyethylene ether and 1g of ethoxylated alkylphenol ammonium sulfate in 100g of deionized water, stir for 30min, slowly add solution 1 under nitrogen conditions, and at the same time drop 10g of 0.003mol / L triethylamine aqueous solution, and adjust the pH to 9.7, increase the system temperature to 80°C, react for 8.5h, and after the reaction is completed, filter, wash, and dry to obtain a composite reinforcing agent.
[0045] Example 3
[0046] Thiolated carbon nitride@MXene QDs were prepared by the following steps:
[0047] Step B1, placing 9 g of urea in an autoclave at 180° C. for 90 min. After the reaction is completed, transferring the product to a muffle furnace, and heating it to 500° C. at 2° C. / min, reacting for 4.5 h. After the reaction is completed, cooling it to room temperature, washing it to neutrality, and then ultrasonically exfoliating it in a mixed solution of ethanol / water with a volume ratio of 1:1 for 12 h, and drying it to obtain carbon nitride nanosheets;
[0048] Step B2, MXene powder and ethanol were added to a mortar at a mass ratio of 1:0.5 and ground for 20 minutes, then sieved with an 800-mesh sieve, 1 g of the sieved MXene material and 2 g of carbon nitride nanosheets were added to a reactor containing 30 g of 0.5 mol / L sodium hydroxide ethanol solution, and stirred in a sealed oil bath at 100 ° C for 3 hours, and then ultrasonically treated for 3 hours. After the reaction was completed, centrifuged at 500 rpm for 30 minutes, the upper layer solution was taken and ultrasonicated for 2 hours, and then dialyzed for 48 hours, and freeze-dried to obtain carbon nitride @MXene QDs;
[0049] Step B3, disperse 1g of carbon nitride @MXene QDs in 50g of deionized water, ultrasonically disperse, and adjust the pH to 8.5, then add 4g of 4-mercaptobenzoic acid, and react under nitrogen for 12h at a reaction temperature of 85°C. After the reaction is completed, cool to room temperature, filter, wash, and dry to obtain thiolated carbon nitride @MXene QDs.
[0050] The composite reinforcing agent is prepared by the following steps:
[0051] Step A1, 0.32 mol of allylamine, 0.4 mol of triethylamine and 100 mL of dichloromethane were added to a reactor and stirred and dispersed, and then 0.3 mol of 4-chlorophenylboric acid was slowly added and stirred for 50 min, and refluxed at 45° C. for 10 h, and continued to react at room temperature for 14 h. After the reaction was completed, centrifugation, washing and drying were performed to obtain intermediate 1;
[0052] Step A2, 0.2 mol of intermediate 1, 0.4 mol of dimethyl phosphate and 200 mL of N,N-dimethylformamide are evenly dispersed in a reactor, the system temperature is raised to 120° C., and the reaction is continued with stirring for 7 hours. After the reaction is completed, the reaction is rotary evaporated and dried to obtain a terminal olefin flame retardant;
[0053] Step A3, add 1g of thiolated carbon nitride @MXene QDs and 3.5g of terminal olefin flame retardant to 100g of deionized water and disperse them evenly, recorded as solution 1; disperse 2g of nonylphenol polyoxyethylene ether and 1g of ethoxylated alkylphenol ammonium sulfate in 100g of deionized water, stir for 30min, slowly add solution 1 under nitrogen conditions, and at the same time drop 10g of 0.005mol / L triethylamine aqueous solution, and adjust the pH to 10, increase the system temperature to 85°C, react for 9h, and after the reaction is completed, filter, wash, and dry to obtain a composite reinforcing agent.
[0054] Example 4
[0055] A method for preparing a degradable automobile recycled plastic product comprises the following steps:
[0056] 50 parts of polylactic acid, 10 parts of automobile recycled plastic particles, 5 parts of the composite reinforcing agent prepared in Example 1, 1 part of KH550, 0.8 parts of antioxidant 1010, 1 part of silicone oil, and 1 part of propylene glycol;
[0057] The raw materials were weighed by weight, and the recycled plastic particles and KH550 were added into a stirrer and stirred evenly. Then, polylactic acid, the composite reinforcing agent prepared in Example 1, antioxidant 1010, silicone oil and propylene glycol were added and mixed evenly. The mixture was transferred to a twin-screw extruder for melt extrusion, water cooling, pelletizing and drying to obtain plastic particles, which were then subjected to tape casting to obtain plastic products.
[0058] Example 5
[0059] A method for preparing a degradable automobile recycled plastic product comprises the following steps:
[0060] 55 parts of polylactic acid, 12 parts of automobile recycled plastic particles, 8 parts of the composite reinforcing agent prepared in Example 2, 1.5 parts of KH550, 0.9 parts of antioxidant 1010, 1.5 parts of silicone oil, and 2 parts of propylene glycol;
[0061] The raw materials were weighed by weight, and the recycled plastic particles and KH550 were added into a stirrer and stirred evenly. Then, polylactic acid, the composite reinforcing agent prepared in Example 2, antioxidant 1010, silicone oil and propylene glycol were added and mixed evenly. The mixture was transferred to a twin-screw extruder for melt extrusion, water cooling, pelletizing and drying to obtain plastic particles, which were then subjected to tape casting to obtain plastic products.
[0062] Example 6
[0063] A method for preparing a degradable automobile recycled plastic product comprises the following steps:
[0064] 60 parts of polylactic acid, 15 parts of automobile recycled plastic particles, 10 parts of the composite reinforcing agent prepared in Example 3, 2 parts of KH550, 1 part of antioxidant 1010, 2 parts of silicone oil, and 3 parts of propylene glycol;
[0065] The raw materials were weighed by weight, and the recycled plastic particles and KH550 were added into a stirrer and stirred evenly. Then, polylactic acid, the composite reinforcing agent prepared in Example 3, antioxidant 1010, silicone oil and propylene glycol were added and mixed evenly. The mixture was transferred to a twin-screw extruder for melt extrusion, water cooling, pelletizing and drying to obtain plastic particles, which were then subjected to tape casting to obtain plastic products.
[0066] Comparative Example 1
[0067] This comparative example is a plastic product, which is different from Example 6 in that the thiolated carbon nitride material is used instead of the thiolated carbon nitride@MXene QDs in the composite reinforcing agent prepared in Example 3, and the rest are the same.
[0068] Comparative Example 2
[0069] This comparative example is a plastic product, which differs from Example 6 in that magnesium hydroxide is used instead of the composite reinforcing agent prepared in Example 3, and the rest are the same.
[0070] The plastic products (films) prepared in Comparative Examples 3-6 and Comparative Examples 1-2 were cut into standard test sizes for performance testing;
[0071] Degradation rate test: Tested in accordance with the domestic biodegradation rate standard GB / T 19277.1-2011;
[0072] Flame retardant performance test: test the limiting oxygen index LOI and vertical burning grade of each film;
[0073] The test results are shown in the following table:
[0074]
[0075]
[0076] As can be seen from the above table, the degradation rate test of the plastic product prepared by the present invention found that the relative biodegradation rate was in the range of 90.6%-91.3% at 90 days, indicating that the plastic product has excellent degradable performance; the flame retardant performance test was also carried out, and it was found that the LOI was in the range of 30.5%-31.3%, and the vertical burning grade was V-0, indicating that the plastic product has excellent flame retardant performance.
[0077] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A degradable automobile recycled plastic product, characterized in that: The raw materials include the following parts by weight: 50-60 parts of polylactic acid, 10-15 parts of automobile recycled plastic particles, 5-10 parts of composite reinforcing agent, 1-2 parts of silane coupling agent, 0.8-1 parts of antioxidant, 1-2 parts of lubricant, and 1-3 parts of toughening agent; The composite reinforcing agent is prepared by the following steps: Step A1, adding allylamine, triethylamine and dichloromethane into a reactor and stirring to disperse, then slowly adding 4-chlorophenylboric acid and stirring for 30-50 minutes, and reflux reaction at 40-45° C. for 6-10 hours, and continue to react at room temperature for 10-14 hours. After the reaction is completed, centrifuge, wash and dry to obtain intermediate 1; Step A2, disperse the intermediate 1, dimethyl phosphate and N,N-dimethylformamide evenly in a reactor, raise the system temperature to 110-120°C, continue stirring and react for 5-7h, and after the reaction is completed, rotary evaporate and dry to obtain a terminal olefin flame retardant; Step A3, add thiolated carbon nitride @MXene QDs and terminal olefin flame retardant into deionized water and disperse them evenly, recorded as solution 1; disperse nonylphenol polyoxyethylene ether and ethoxylated alkylphenol ammonium sulfate in deionized water, stir for 30 minutes, slowly add solution 1 under nitrogen conditions, and at the same time drop 0.001-0.005 mol / L triethylamine aqueous solution, and adjust the pH to 9.5-10, increase the system temperature to 75-85 ° C, react for 8-9 hours, and after the reaction is completed, filter, wash and dry to obtain a composite reinforcing agent.
2. The degradable automobile recycled plastic product according to claim 1, characterized in that: In step A1, the usage ratio of allylamine, triethylamine, dichloromethane and 4-chlorophenylboric acid is 0.12-0.32 mol: 0.15-0.4 mol: 100 mL: 0.1-0.3 mol.
3. The degradable automobile recycled plastic product according to claim 1, characterized in that: In step A2, the usage ratio of intermediate 1, dimethyl phosphate and N,N-dimethylformamide is 0.1-0.2 mol: 0.2-0.4 mol: 200 mL.
4. The degradable automobile recycled plastic product according to claim 1, characterized in that: In step A3, the mass ratio of nonylphenol polyoxyethylene ether, ethoxylated alkylphenol ammonium sulfate, deionized water, solution 1 and triethylamine aqueous solution is 1-2:1:100:100:10; the amount ratio of thiolated carbon nitride @MXene QDs, terminal olefin flame retardant and deionized water in solution 1 is 1g:2.5-3.5g:100g.
5. The degradable automobile recycled plastic product according to claim 1, characterized in that: The thiolated carbon nitride@MXene QDs were prepared by the following steps: Step B1, placing 6-9 g of urea in an autoclave at 180° C. for 60-90 min. After the reaction is completed, transferring the product to a muffle furnace and heating it to 500° C. at a rate of 2° C. / min. reacting for 3.5-4.5 h. After the reaction is completed, cooling to room temperature, washing to neutrality, and then ultrasonically exfoliating in a mixed solution of ethanol / water with a volume ratio of 1:1 for 6-12 h, and drying to obtain carbon nitride nanosheets; Step B2, MXene powder and ethanol were added to a mortar at a mass ratio of 1:0.5 and ground for 20 minutes, then sieved with an 800-mesh sieve, and the sieved MXene material and carbon nitride nanosheets were added to a reactor containing 0.5 mol / L sodium hydroxide ethanol solution, and stirred in a sealed oil bath at 100°C for 3 hours, and then ultrasonically treated for 2-3 hours. After the reaction was completed, centrifuged at a speed of 300-500 rpm for 30 minutes, and the upper layer solution was ultrasonically treated for 2 hours, and then dialyzed for 48 hours, and freeze-dried to obtain carbon nitride @MXene QDs; Step B3, disperse the carbon nitride @MXene QDs in deionized water, ultrasonically disperse, and adjust the pH to 8.5, then add 4-mercaptobenzoic acid, and react under nitrogen conditions for 10-12 hours at a reaction temperature of 75-85°C. After the reaction is completed, cool to room temperature, filter, wash, and dry to obtain thiolated carbon nitride @MXene QDs.
6. The degradable automobile recycled plastic product according to claim 5, characterized in that: The mass ratio of the MXene material, carbon nitride nanosheets and sodium hydroxide ethanol solution after screening in step B2 is 1:0.5-2:
30.
7. The degradable automobile recycled plastic product according to claim 5, characterized in that: In step B3, the mass ratio of carbon nitride@MXene QDs, 4-mercaptobenzoic acid and deionized water is 1:2-4:
50.
8. The method for preparing a degradable automobile recycled plastic product according to claim 1, characterized in that: The following steps are involved: The raw materials are weighed by weight, and recycled plastic particles from automobiles and silane coupling agent are added into a stirrer and stirred evenly. Then polylactic acid, composite reinforcing agent, antioxidant, lubricant and toughening agent are added and mixed evenly. The mixture is then transferred into a twin-screw extruder for melt extrusion, water cooling, pelletizing and drying to obtain plastic particles, which are then subjected to tape casting to obtain plastic products.
Citation Information
Cited By
Environment-friendly degradable bio-based material and preparation method thereof
CN119978748A